2005
DOI: 10.1016/j.femsyr.2005.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Increased nuclear envelope permeability and Pep4p-dependent degradation of nucleoporins during hydrogen peroxide-induced cell death

Abstract: The death of yeast treated with hydrogen peroxide (H(2)O(2)) shares a number of morphological and biochemical features with mammalian apoptosis. In this study, we report that the permeability of yeast nuclear envelopes (NE) increased during H(2)O(2)-induced cell death. Similar phenomena have been observed during apoptosis in mammalian tissue culture cells. Increased NE permeability in yeast was temporally correlated with an increase in the production of reactive-oxygen species (ROS). Later, after ROS levels be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 49 publications
3
47
2
1
Order By: Relevance
“…It localizes predominantly to the vacuolar compartment, but translocation of this protease from the vacuole to the cytosol has been described. The active enzyme migrates from the vacuole in H 2 O 2 -triggered apoptotic cells (41). Translocation is associated with an increase in vacuolar permeability.…”
Section: Discussionmentioning
confidence: 99%
“…It localizes predominantly to the vacuolar compartment, but translocation of this protease from the vacuole to the cytosol has been described. The active enzyme migrates from the vacuole in H 2 O 2 -triggered apoptotic cells (41). Translocation is associated with an increase in vacuolar permeability.…”
Section: Discussionmentioning
confidence: 99%
“…The present study identified several genes associated with protein folding and stabilization that are upregulated during recovery after H 2 O 2 stress, and therefore, might be important for the selective import of oxidized proteins into the vacuole. However, it has recently been shown that cells treated with H 2 O 2 release Pep4p into the cytoplasm (Mason et al, 2005). It is therefore conceivable that oxidized proteins may be degraded by Pep4p in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Pep4p (the homolog of mammalian cathepsin-D) has been shown to migrate out of the vacuoles and degrade nucleoporins upon H 2 O 2 -induced cell death. 84 However, the associated form(s) of death remains to be accurately characterized.…”
Section: Proteins and Pathways Regulating Yeast Apoptosismentioning
confidence: 99%